Sludge curing material and preparation method thereof

By mixing phosphogypsum with sludge and using lime and slag as curing agents, the problems of high treatment costs and unstable curing efficiency in the existing sludge curing technology are solved, and high-strength sludge curing materials are achieved, which is of great economical importance and Environmental benefits.

CN119462052AInactive Publication Date: 2025-02-18WUHAN INST OF TECH

Patent Information

Application Number
CN202411661287.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sludge curing technology has problems such as high treatment cost, unstable curing efficiency, possible secondary pollution, and limited utilization methods of cured products.

Method used

A mixture of phosphogypsum and sludge is used and cured by a mixture of lime and slag as a curing agent to form a high-strength sludge curing material.

Benefits of technology

It achieves better technical effects than cement, reduces cement consumption, improves the stability and strength of sludge, and has important economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a sludge curing material and a preparation method thereof, and relates to the technical field of geotechnical engineering. The preparation method of the sludge curing material comprises the following steps: (1) mixing ardealite and sludge to obtain mixed sludge; (2) adding a curing agent into the mixed sludge, and curing to obtain the sludge curing material, the curing agent is a mixture of lime and slag. The lime and the slag are used as curing agents to cure the mixture of the ardealite and the sludge, and the strength of the obtained curing material is far higher than that of a pure cement curing material. The method provided by the invention can realize recycling of industrial wastes, namely ardealite and slag, and has important economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geotechnical engineering, and in particular to a sludge solidification material and a preparation method thereof. Background Art

[0002] Sludge solidification technology is a treatment method that converts water-containing sludge into stable solids through physical, chemical or biological means. It is widely used in the fields of environmental pollution control and resource recycling. The main advantage of this technology is that it can significantly reduce the volume of sludge, reduce the water content, and improve the stability and safety of sludge, so as to facilitate subsequent transportation, stacking and utilization, such as land reclamation and construction material production. However, sludge solidification technology also faces many challenges. First, the treatment cost is high, especially when it is applied on a large scale, economic efficiency becomes a constraint. Secondly, the solidification efficiency may be affected by the composition of the sludge and external conditions, resulting in unstable effects. In addition, secondary pollution may occur during the solidification process, such as the release of harmful gases or residual harmful substances in the solidified products, which requires strengthened monitoring and management. The utilization of solidified products is limited, and market demand and regulatory standards are not yet perfect, which restricts its promotion and application. Therefore, while promoting sludge solidification technology, it is necessary to comprehensively consider environmental benefits, economic costs and technical feasibility, and continuously optimize and innovate to achieve more efficient and environmentally friendly sludge treatment and resource utilization.

[0003] As a byproduct of the phosphate fertilizer industry, phosphogypsum is produced in huge quantities, and its treatment and utilization are currently an environmental problem that needs to be solved urgently. Traditional phosphogypsum accumulation not only occupies a large amount of land, but also may cause environmental pollution, such as the spread of heavy metals and radioactive elements. Therefore, it is of great significance to explore its resource utilization. On the other hand, with the acceleration of urbanization, a large amount of silt is produced during river dredging and land reclamation, and these silts also face disposal difficulties. Silt has the characteristics of high water content and low strength, and direct stacking or landfilling is likely to cause environmental and safety problems. Therefore, using phosphogypsum to solidify silt can not only effectively utilize industrial waste and reduce environmental pollution, but also improve the performance of silt, and realize the coordinated disposal and resource utilization of waste. This research not only has important environmental protection significance, but also has broad application prospects in the field of solid waste resource technology. Summary of the invention

[0004] The purpose of the present invention is to provide a sludge solidification material and a preparation method thereof to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a method for preparing a sludge solidification material, comprising the following steps:

[0007] (1) mixing phosphogypsum and sludge to obtain mixed sludge;

[0008] (2) adding a curing agent to the mixed sludge and curing the mixed sludge to obtain the sludge solidified material;

[0009] The solidifying agent is a mixture of lime and slag.

[0010] Furthermore, the water content of the mixed sludge is 60%-120%.

[0011] Furthermore, the mass ratio of the phosphogypsum to the solid matter in the mixed sludge is 0-5:5-10.

[0012] Furthermore, the mass ratio of the lime to the slag is 1-5:5-9.

[0013] Furthermore, the added amount of the curing agent is 6%-18% of the mass of the solid matter in the mixed sludge.

[0014] Furthermore, the mass ratio of the phosphogypsum to the solid matter in the mixed sludge is 0%, 10%, 20%, 30%, 40% or 50%.

[0015] Furthermore, the mass ratio of the lime to the slag is 5:5, 4:6, 3:7, 2:8 or 1:9.

[0016] The present invention also provides a sludge solidification material prepared by the above preparation method.

[0017] In the first stage of the experiment of the present invention, the curing effects of 5 different proportions of curing agents on different proportions of phosphogypsum mixed sludge were studied; in the second stage, lime: slag = 2:8 (the strength of the mixed sludge under this curing agent ratio is the highest, and the ratio of the mixed sludge with the highest strength is: phosphogypsum: soil = 1:9, that is, phosphogypsum accounts for 10% of the mixed sludge), and the curing effects under different curing agent dosages (6%, 9%, 12%, 15%, 18%) and different moisture contents of the mixed sludge (60%, 75%, 90%, 105%, 120%) under this proportion are studied.

[0018] (1) Based on the results of the first phase of the test, the optimal ratio of lime: slag and the appropriate amount of phosphogypsum can be obtained;

[0019] (2) According to the optimal dosage:

[0020] 1) Changing the curing agent dosage from 6% to 18%, the strength increased from more than 200 kPa to more than 3,000 kPa;

[0021] 2) Changing the moisture content of the mixed sludge from 60% to 120%, and reducing the strength from more than 3,000 kPa to more than 200 kPa.

[0022] The present invention summarizes the strength variation characteristics of sludge solidified by lime, slag and phosphogypsum. In engineering, the curing agent and phosphogypsum with appropriate dosage can be selected according to the different sludge moisture content in different sites, the different requirements for the strength of embankment fillers, and the different solid waste treatment amounts (i.e. the dosage of phosphogypsum, mainly phosphogypsum), which has reference significance.

[0023] The present invention uses slag and lime to solidify the mixture of phosphogypsum and sludge without using cement, which can achieve a better technical effect than cement. The present invention reduces cement consumption while increasing industrial waste slag treatment.

[0024] In the present invention, lime and slag are used as curing agents, wherein lime has three main functions: first, hydration provides a certain strength, second, providing an alkaline environment to stimulate the activity of slag, and third, providing hydrated calcium aluminate that can react with phosphogypsum to form ettringite after hydration. Slag has two main functions: first, hydration provides higher strength after being stimulated, and second, providing hydrated calcium aluminate that can react with phosphogypsum to form ettringite after hydration.

[0025] The products of lime and slag hydration are mainly calcium hydroxide, hydrated calcium silicate, hydrated calcium aluminate and other compounds. After the various hydrates are generated, some of them continue to harden themselves to form a skeleton with a certain strength. While providing a certain strength, the hydrated calcium aluminate generated by reacting with the soil in the silt can react with Ca(SO)4.2H2O in the phosphogypsum component to form ettringite. ettringite needs to combine with 32 water molecules, and the chemical reaction formula is:

[0026] 3CaO·Al2O3·nH2O+3CaSO4·2H2O+(26-n)H2O→3CaO·Al2O3·3CaSO4·32H2O

[0027] Calcium aluminate is a needle-shaped crystal with a hexagonal cross section. It expands in volume during its formation, and the solid phase volume can increase by about 120%. On the one hand, the product Calcium aluminate itself and its expansion can fill part of the pores, reduce the pore volume of the solidified soil, and reduce the average pore size of the solidified soil, which has a "filling and compacting" effect.

[0028] With the addition of phosphogypsum, lime and slag are hydrated to solidify the sludge. The phosphogypsum in the mixed sludge is a sulfate, which can stimulate the activity of slag in an alkaline environment, thereby further improving the strength of the mineralized soil to meet the strength requirements of roadbed fillers. At the same time, the present invention can also realize the reuse of phosphogypsum as industrial waste, which has important economic and environmental benefits.

[0029] The invention obtains the influence law of strength of engineering soft soil with different proportions of lime and slag and different dosages of phosphogypsum in a relatively comprehensive manner, and on the basis of the optimal proportion, obtains the change law of strength when the moisture content changes from low to high and the dosage changes from low to high, and compares the strength of cement-solidified sludge. In engineering, it can provide a reference basis for the solidification effect of sludge with different moisture contents by composite solidification of phosphogypsum.

[0030] The present invention discloses the following technical effects:

[0031] The present invention uses lime and slag as curing agents to solidify the mixture of phosphogypsum and sludge, and the strength of the obtained solidified material is much higher than that of the pure cement solidified material.

[0032] The invention can realize the recycling of industrial waste phosphogypsum and slag, and has important economic and environmental benefits. DETAILED DESCRIPTION

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0038] The lime used in the embodiment of the present invention is slaked lime, which is obtained from a factory in Guangzhou, and has a calcium hydroxide content of 93.46% and a 200-mesh pass rate of 96.14%.

[0039] The slag used in the embodiment of the present invention is S105 grade slag, which is taken from a factory in Henan Province and has a specific surface area of ​​628m 2 / kg, fluidity ratio is 102%, 7d and 28d activity index are 98% and 115% respectively, density is 2.93g / cm 3 .

[0040] Example 1

[0041] The steps of the present invention are as follows:

[0042] (1) Preparation of target moisture content sludge and phosphogypsum mixed sludge:

[0043] The present invention adopts a relatively simple method for preparing the phosphogypsum mixed sludge, that is, directly calculating the amount of phosphogypsum and water to be added after obtaining the original sludge. If the water content of the final prepared mixed sludge is 75%, the water content of the target sludge to be configured is 70%, and the other 5% of the mass of water is reserved for dissolving the curing agent.

[0044] First, if the target sludge to be prepared is 70%, the moisture content of the prepared engineering soft soil (less than 70%, hereinafter referred to as original sludge) is first measured, and the engineering soft soil is configured into soft soil with the target moisture content. The mass of water to be added is calculated, and then the calculated mass of water is added to mix and stir into the target sludge with a moisture content of 70%.

[0045] If phosphogypsum mixed sludge is to be prepared, and if the mass of phosphogypsum accounts for 10% of the total mass of solid matter in the phosphogypsum mixed sludge, then the phosphogypsum mixed sludge is prepared by mixing 90% of the mass of the target sludge with a moisture content of 70% and 10% of the mass of the phosphogypsum with a moisture content of 70% uniformly. First, calculate the mass of the original sludge corresponding to the 90% mass of the sludge with a moisture content of 70% (dry soil mass). Since there is a difference in moisture content between the original sludge and the sludge with the target moisture content, it is reflected in the mass difference. The mass difference is the mass of water that needs to be added additionally. Add this part of water and the water required to prepare the phosphogypsum with a moisture content of 70% to the phosphogypsum, mix and stir evenly, and then add 90% of the mass of the target sludge with a moisture content of 70% and stir evenly. In this way, the phosphogypsum mixed sludge is prepared and stored for 48 hours.

[0046] (2) Weigh lime and slag:

[0047] The total amount of curing agent is 15% of the total mass of solid matter in the phosphogypsum mixed sludge. For example, when the ratio of lime to slag is 1:9, the lime accounts for 10% of the total amount of curing agent and the slag accounts for 90% of the total amount of curing agent. Weigh the corresponding mass of curing agent, put it into the reserved 5% mass of water, mix and stir evenly to prepare a curing agent mixture.

[0048] (3) The phosphogypsum mixed sludge obtained in step (1) and the curing agent mixture obtained in step (2) are mixed together, stirred and mixed evenly with a stirrer, and then loaded into a PVC plastic pipe to make a standard unconfined compressive strength test block and a direct shear test block.

[0049] (4) After the specimens are cured to a certain age, the unconfined compressive strength and shear strength tests are carried out.

[0050] According to different proportions of the curing agent, the curing agents are divided into five groups, as shown in Table 1, wherein the proportions of the curing agent are: lime: slag = 5:5, 4:6, 3:7, 2:8 or 1:9.

[0051] Table 1 Ratio of different curing agents

[0052]

[0053] Each of the five groups in Table 1 is divided into six subgroups according to the proportion of phosphogypsum in the solid matter of the phosphogypsum mixed sludge, and the proportion of phosphogypsum is 0%, 10%, 20%, 30%, 40% and 50% respectively. Specifically, the division of the six subgroups of Group 1 in Table 1 is shown in Table 2.

[0054] Table 2 Different proportions of phosphogypsum at the same curing agent dosage

[0055]

[0056] The “soil” in Table 2 refers to the content of solid matter in the original sludge.

[0057] Table 3 shows the unconfined compressive strength of each subgroup in Table 2.

[0058] Table 3 Unconfined compressive strength of different groups (unconfined compressive strength q u / kPa)

[0059]

[0060]

[0061] It can be seen that the best ratio of lime: slag is 2:8, and in different ratios of lime to slag, phosphogypsum corresponds to different optimal dosages, and 10% is a more suitable dosage. The test results are shown in Table 3. Except for the working condition where the curing agent ratio is 1:9, the optimal dosage of phosphogypsum is not 10%, but increases with the increase of phosphogypsum dosage. Under other ratios, when the phosphogypsum dosage is 10%, the strength can reach a larger value. Therefore, when the curing agent ratio ranges from 5:5 to 2:8, the optimal dosage of phosphogypsum is within 20%. Ding Jianwen, Zhang Shuai, Hong Zhenshun, et al., "Experimental study on cement-phosphogypsum dual-mixing solidification treatment of high-water content dredged sludge [J]. Rock and Soil Mechanics, 2010, 31(9): 2817-2822." The optimal dosage of phosphogypsum in cement-phosphogypsum solidification of sludge is 30% of cement. The cement dosage of the control group in this experiment is 15%, so the optimal dosage of phosphogypsum in the control group is about 5%. Although the 10% dosage in this experiment has exceeded the optimal dosage, it is still the maximum strength control group of the cement group in this experiment.

[0062] Effects of different curing agent dosages and different phosphogypsum mixed sludge moisture content on strength:

[0063] Based on the above tests, two working conditions were analyzed: lime: slag = 2:8 and phosphogypsum dosage of 10%, and the effects of dosage and moisture content on the unconfined compressive strength were studied respectively.

[0064] Table 4 Different curing agent dosage ratio

[0065]

[0066] Table 5 Test results of different curing agent dosage ratios (unconfined compressive strength q u / kPa)

[0067]

[0068] Table 5 shows the variation of the unconfined compressive strength of the test blocks under 5 different curing agent dosages.

[0069] Table 6 Moisture content ratio of different sludge mixtures

[0070]

[0071] Table 7 Moisture content test results (unconfined compressive strength q u / kPa)

[0072]

[0073] It can be seen from Table 7 that the unconfined compressive strength variation of the test blocks under five different mixture moisture contents.

[0074] Table 8 Chemical composition of phosphogypsum (PG)

[0075]

[0076] Table 9 Particle size distribution of phosphogypsum (PG)

[0077]

[0078] Table 10 Cement performance indicators

[0079]

[0080] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a sludge solidification material, characterized in that: The following steps are involved: (1) mixing phosphogypsum and sludge to obtain mixed sludge; (2) adding a curing agent to the mixed sludge and curing the mixed sludge to obtain the sludge solidified material; The solidifying agent is a mixture of lime and slag.

2. The preparation method according to claim 1, characterized in that: The water content of the mixed sludge is 60%-120%.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the phosphogypsum to the solid matter in the mixed sludge is 0-5:5-10.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the lime to the slag is 1-5:5-9.

5. The preparation method according to claim 1, characterized in that: The added amount of the solidifying agent is 6%-18% of the mass of the solid matter in the mixed sludge.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the phosphogypsum to the solid matter in the mixed sludge is 0%, 10%, 20%, 30%, 40% or 50%.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the lime to the slag is 5:5, 4:6, 3:7, 2:8 or 1:

9.

8. The sludge solidification material prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Phosphogypsum-sludge combined curing treatment method

    CN101579683A

  • Sludge curing material for comprehensively utilizing phosphorous gypsum

    CN103539423A

  • Sludge curing agent and device for curing sludge by using sludge curing agent

    CN116003082A

Cited By

  • A high-efficiency utilization method for river sludge based on dredging-filling integration

    CN122685289A